Factorisation using common factors

Factorization by common factors

Ex 12.1, 1 (i)

Ex 12.1, 1 (ii)

Ex 12.1, 1 (iii) Important

Ex 12.1, 1 (iv) Important

Ex 12.1, 1 (v)

Ex 12.1, 1 (vi) Important

Ex 12.1, 1 (vii)

Ex 12.1, 1 (viii) Important

Example 2 Important

Example 1

Ex 12.1, 2 (i)

Ex 12.1, 2 (ii) Important

Ex 12.1, 2 (iii)

Ex 12.1, 2 (iv) Important

Ex 12.1, 2 (v)

Ex 12.1, 2 (vi)

Ex 12.1, 2 (vii)

Ex 12.1, 2 (viii) Important

Ex 12.1, 2 (ix) You are here

Ex 12.1, 2 (x) Important

Last updated at April 16, 2024 by Teachoo

Ex 12.1, 2 (Method 1) Factorise the following expressions. (ix) đĽ^2 y z + x đŚ^2z + x y đ§^2đĽ^2 y z + x đŚ^2z + x y đ§^2 = (đĽ Ă đyz) + (y Ă đyz) + (z Ă đyz) Taking đyz common, = đyz (đ + y + z) Ex 12.1, 2 (Method 2) Factorise the following expressions. (ix) đĽ^2 y z + x đŚ^2z + x y đ§^2 đĽ^2 y z ăđĽđŚă^2z đĽyđ§^2 So, x, y and z are the common factors. đĽ^2 y z + đĽđŚ^2z + đĽyđ§^2 = (đĽ Ă đĽ Ă y Ă z) + (đĽ Ă y Ă y Ă z) + (đĽ Ă y Ă z Ă z) Taking đ Ă y Ă z common, = đĽ Ă y Ă z Ă (đĽ + y + z) = đyz (đ + y + z) = đĽ^2 Ă y Ă z = đĽ Ă đŚ^2 Ă z = đĽ Ă y Ă đ§^2 = đ Ă đ Ă y Ă z = đ Ă y Ă y Ă z = đ Ă y Ă z Ă z